Power grid electricity prediction model in multi-dimensional scenarios. Issue 1 (1st January 2022) - Mei, D; Guo, SM; Li, YR
Abstract: The prediction of power grid electricity is the key to ensure the reliable and economic operation of power system. In order to improve the accuracy of power grid electricity forecast, a new power grid electricity forecast model in multi-dimensional scenarios is proposed in this paper. The simulation results show that this method has higher prediction accuracy, and it provides a new idea for the research of power grid electricity prediction